Mine backfilling to limit surface subsidence: a case history - G. G. Marino; K. A. Patel; P. H. Carr (The Institute of Materials, Minerals and Mining, 1905)
Extensions to a correctional institution at Wabash Valley, Indiana, required development over abandoned coal-mine workings, at 90 m depth, where subsidence was possible at surface. Backfilling of the flooded mine in critical areas was determined to be the most cost-effective method of limiting the risk of damage to the buildings. Containment grout was first placed in selected entries and cross-cuts of each mine area; the remaining volume was then filled with a readily flowing infill grout. Where a high proportion of an area was taken up by rubble, calcium lignosulphonate was used as a retarder and plasticiser to increase penetration. Grout movement was monitored from adjacent boreholes with an electrical resistivity probe during grouting, while after the work was finished core samples were obtained from verification holes drilled in the backfilled areas